EFFECTS OF HAPPINESS TRAINING ON MENTAL HEALTH IN ADULTS: A SYSTEMATIC REVIEW - Sonia Khodabakhsh, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Past studies have shown mental health and happiness are associated with each other. Several studies were done on the effectiveness of happiness training in several aspects. In this review paper, the effect of happiness training on mental health among adults is systematically reviewed. Through a search in Web of Science, PubMed, and Google Scholar using the â€œhappiness trainingâ€ keyword and its related words among post-2005 publications, the number of 18 research articles included in this review paper. Based on the systematic review, 18 variables in the selected studies are discussed which include anxiety, blood pressure, burnout, depression, emotions, flourishing, happiness, life expectancy, life satisfaction, migraine symptoms, mindfulness, quality of life, resilience, stress, tolerance, and well-being.